Production of ?-amylase by Bacillus amyloliquefaciens under solid state fermentation - Uygut, Muhammet Ali; Tanyıldızı, Muhammet Şaban; Topdemir, Aykut; Kalender, Mehmet (My University, 2015)
Over the last two decades, solid state fermentation (SSF) has gained significant attention for the development of industrial bioprocesses, particularly due to lower energy requirement associated with higher product yields and less wastewater production. SSF is a three-phase heterogeneous process, comprising solid, liquid and gaseous phases, which offers potential benefits for the microbial cultivation for bioprocesses and products development. SSF has tremendous potential for the production of enzymes not only for laboratory but also for commercial production. The fruit processing industries produce a large amount of waste in the form of peel and pulp. Orange peel(OP) is that abundant waste of juice industry was used as substrate for production of ?-amylase. Different parameters such as initial moisture level (%), concentration of starch and peptone (g/ 10 g dry substrate) and whey (ml/10 g dry substrate) were investigated for ?- amylase production. Design Expert 8.0 is used for experimental design and optimization. Studies were carried out in flask erlenmayers (250 ml) at 33 °C as static. ?-Amylase was assayed by colorimetric method (Bernfeld, 1955). A marked improvement in enzyme production (105,881 U/ml) was achieved by optimization of moisture level (%81,38), concentration of starch (1,49 g/ 10 g dry substrate) and peptone (1,50 g/ 10 g dry substrate) and whey (1,40 ml/10 g dry substrate). The results indicated that the production of ?-amylase was great option in the medium using OP and whey. OP, an inexpensive by-product of food industry, was found suitable for SSF and a good substrate for ?-amylase production.
Bildiri - Yayımlanmamış
Keywords: ?-Amylase; Orange peel; Solid state fermentation; Response surface methodology